(untitled) (EFEI (Educación Física Experiencias e Investigaciones), 2022)
This analytical and descriptive work aims to present the picture of the situation in 2022 of undergraduate training in Physical Education in Argentina. Based on the systematization of the different training proposals, curricular designs and normative frameworks. Their territorial distribution, their enrolment in the higher education system, the prevailing conceptual guidelines, training horizons and institutional circulation are analysed. The presentation seeks to establish dialogues between the situation of Physical Education and the rest of the educational proposals of the higher level, in order to begin to trace their particularities and their common points.